Growth challenges of SMEs: empirical evidence in Sabah, Malaysia / Sylvia Nabila Azwa Ambad, Jasmine Vivienne Andrew and Dayang Haryani Diana Awang Amit - Ambad, Sylvia Nabila Azwa; Andrew, Jasmine Vivienne; Awang Amit, Dayang Haryani Diana (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Small Medium Enterprises (SMEs) are currently facing a more challenging business environment due to the fast-changing customer preferences, globalization, stiff competition, limited resources, and human resources issues, among others. The failure rate of SMEs in Malaysia is alarming, whereby 60% of the new SMEs fail within five years of establishment. Additionally, only 4 out of 10 SMEs are able to successfully meet the challenges associated with growth. The SMEs barriers to growth have been a long-unsolved problem in this country. Therefore, this paper aims to explore the barriers to business growth among SMEs. Face-to-face interviews with the founders of the businesses were conducted. Eleven entrepreneurs were interviewed in Kota Kinabalu, Sabah, Malaysia. It was found that there are five main barriers to business growth namely; financial issues, human resources problems, marketing strategies, facilities, appliances and layout and problems with suppliers. This paper offers recommendations to SMEs to overcome the barriers to growth.